Belarusian Scientific School “Gears” - Victor E. Starzhinsky; Sergey V. Shil’ko; Nikolay N. Ishin (Механика машин, механизмов и материалов)
Information is presented on Belarusian scientific school “Gears” (I.S. Tsitovich, O.V. Berestnev, V.B. Algin, V.E. Antonyuk etc.) from the moment of its origin in 1973 at the Joint Institute of Mechanical Engineering of the NAS of Belarus (at that time – Institute of Machine Study of the Academy of Sciences of the BSSR) and further development at the mentioned Institute, as well as at the V.A. Belyi Metal Polymer Research Institute of the NAS of Belarus (V.E. Starzhinsky, S.V. Shil’ko etc.) and Belarusian-Russian University (P.N. Gromyko, A.M. Dankov, M.E. Lustenkov etc.). The paper is provided with references to articles, monographs and textbooks detailing the subject matter and authorship of these publications.